THE OTHER MOROCCO: HOW AMERICA PERCEIVES THE ORIENT - El Mitry , Abdelghani (International Journal of Language and Literary Studies, 2023)
This paper examines the portrayal of Morocco in American culture throughout different historical periods. Its main objective is to provide a critical analysis of cultural encounters, particularly focusing on how the American perspective shapes the representation of Morocco as the “Other.” The aim of this paper is not only to highlight the various textual and visual depictions influenced by Orientalist discourse used to represent the country and its people, but also to explore America's historical involvement in the narrative of Orientalism. The examination of American and Western perceptions of Morocco leads to a discussion on Edward Said’s Orientalism, reconsidering some of its theoretical limitations. Specifically, Said's neglect of American Orientalist knowledge systems and the oversight of American fair exhibits in shaping popular Victorian perceptions of the Orient. The paper also addresses Orientalism’s failure to critically engage with the agency of natives within an orientalized context and its limited exploration of how the Oriental Other, when displaced to the center, reacts and acts, as well as the implications of the Orient transitioning from the “Other” to the “Self” and from the margins to the center of the paradigm